EVALUASI PENERAPAN SISTEM INFORMASI MANAJEMEN DI LPK ALFA PRIMA MENGGUNAKAN FRAMEWORK COBIT 5 - Putu Trisna Hady Permana S (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
This study aims to evaluate the performance of management information systems at the Alfa Prima Job Training Institute using the COBIT 5 framework. COBIT is a framework that provides standards in a domain framework consisting of a set of IT processes that represent activities that can be controlled and structured. COBIT was issued by ISACA in 1992 and is a process-oriented standard focused on business goals and a managerial and technical tool for IT units. In this study, an evaluation of the performance of management information systems at the Alfa Prima Job Training Institute will be carried out using the COBIT 5 framework, resulting in assessments and recommendations that the Alfa Prima Job Training Institute will use to improve performance in the application of IS and IT governance.